Probing the Effect of Governance of Tourism Development, Economic Growth, and Foreign Direct Investment on Carbon Dioxide Emissions in Africa: The African Experience - Agyeman, Fredrick Oteng; Zhiqiang, Ma; Li, Mingxing; Sampene, Agyemang Kwasi; Dapaah, Malcom Frimpong; Kedjanyi, Emmanuel Adu Gyamfi; Buabeng, Paul; Li, Yiyao; Hakro, Saifullah; Heydari, Mohammad (Energies (Basel), 2022)
The environmental repercussions of extensive carbon dioxide (CO2) emissions on the environment are crucial for policymakers and scholars. The repercussions of and connection between economic growth (ECG), tourism (TOUR), and foreign direct investment (FDI) on CO2 emission mitigation have been measured and argued from empirical and theoretical perspectives by scholars. Notwithstanding, the extant body of knowledge has failed to incorporate and investigate the function of governance in decarbonizing tourism activities and FDI from CO2 emissions to attain a healthy and quality environment in Africa. Hence, this current research investigates governance’s role in the reduction processes of CO2 emissions grounded in environmental Kuznets curve (EKC) conceptual assumptions for panel data spanning 2000 through 2020 for 27 African countries. This research utilized the Westerlund panel cointegration approach for the investigation of the cointegration of the selected variables. This study applied the Driscoll–Kraay regression approach for the long-term estimation. In addition, the dynamic ordinary least squares (DOLS) and the pooled mean group (PMG) were used for robustness checks. The findings of this research indicated that the governance (GOV) indicators employed have a statistically significant effect on the CO2 emission reduction. Besides, this study found that the appreciation of the income of the nations gives credence to the formation of the EKC theory and contributes to the decline in CO2 emissions within the selected African nations. The findings revealed that tourism, FDI, ECG, and GOV are positive and significant factors leading to increased CO2 emissions in Africa. Furthermore, the results showed that effective governance and control of FDI inflows and tourism activities can support decarbonization. These findings suggest the merits of governance in ensuring effective decarbonization policies of the environment, and policy suggestions are accordingly put forward.